2020
DOI: 10.1093/gerona/glaa221
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Olfactory Decline in Aging: A Longitudinal Population-Based Study

Abstract: Background Olfactory dysfunction is common in aging and associated with dementia and mortality. However, longitudinal studies tracking change in olfactory ability are scarce. We sought to identify predictors of interindividual differences in rate of olfactory identification change in aging Methods Participants were 1,780 individuals, without dementia at baseline and with at least two olfactory assessments over 12 years of fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 48 publications
5
36
0
Order By: Relevance
“…The lack of statistical significance was likely attributable to the small sample size with resulting low power in this group. Although olfactory function decreased significantly as a function of time (annual change rate of À0.213; p < .001), as described in detail elsewhere (Ekstr€ om et al, 2020), no statistically significant associations between CRP levels at baseline and olfactory change were observed (ps > .406).…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…The lack of statistical significance was likely attributable to the small sample size with resulting low power in this group. Although olfactory function decreased significantly as a function of time (annual change rate of À0.213; p < .001), as described in detail elsewhere (Ekstr€ om et al, 2020), no statistically significant associations between CRP levels at baseline and olfactory change were observed (ps > .406).…”
Section: Resultssupporting
confidence: 51%
“…Interestingly, sensitivity analyses showed that associations between CRP and olfactory function were confined to participants aged 72 years and below and males. Increasing age is a principal cause for olfactory loss (Doty & Kamath, 2014;Ekstr€ om et al, 2020), which may over-shadow potential effects of inflammatory processes on olfactory ability in older age groups. Alternatively, and as mentioned earlier, potential influences of inflammation on olfaction may be exerted before a certain age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common etiologies of olfactory disorders among patients seeking medical attention at ear, nose, and throat clinics include upper respiratory infection, chronic sinusitis, nasal polyposis, allergic rhinitis, and head trauma ( Brämerson et al., 2007 ; Temmel et al., 2002 ). The presence of type-2 diabetes accelerates age-related olfactory decline ( Ekström et al., 2020 ; Olofsson et al., 2010 ). Given the profound impact of such conditions on the olfactory system, it is not surprising that environmental variables overshadow genetic variables in their effects of olfactory abilities among aging individuals ( Doty & Kamath, 2014 ; Rawson, 2006 ).…”
Section: Environment and Geneticsmentioning
confidence: 99%
“…The most common etiologies of olfactory disorders among patients seeking medical attention at ear, nose and throat clinics include upper respiratory infection, chronic sinusitis, nasal polyposis, allergic rhinitis, and head trauma (Temmel et al, 2002;Brämerson et al, 2007). The presence of type-2 diabetes accelerates age-related olfactory decline (Ekström et al, 2020;Olofsson et al, 2010). Given the profound impact of such conditions on the olfactory system, it is not surprising that environmental variables overshadow genetic variables in their effects of olfactory abilities among older individuals (Rawson, 2006;Doty and Kamath, 2014).…”
Section: Environment and Geneticsmentioning
confidence: 99%